Deposit Strategy of Easy Wadiah Savings Fund at Bank Syariah Indonesia - Mohammad Yusuf; Annisa Sanny; Zuhri Ramadhan (Lead Journal of Economy and Administration, 2024)
This study aims to find out about the development of Islamic banks in Indonesia. This research is qualitative descriptive. This study included literature to examine the written sources such as scientific journals, books referesni, literature, encyclopedias, scientific articles, scientific papers and other sources that are relevant and related to the object being studied. As for the object of study of this research is in the form of texts or writings that describe and explain about the development of Islamic banks in Indonesia. Results from this study is Indonesian banking now enlivened by the presence of Islamic banks, which offers financial products and investment in a different way than conventional banks, as Indonesia is the largest Muslim country in the world. The development of Islamic banking in Indonesia has become a benchmark for the success of the Islamic economic existence. Bank Muamalat as the first Islamic bank and a pioneer for other Islamic banks in Indonesia.